Soziale Beschleunigung in nicht-westlichen Gesellschaften: Eine Fallstudie zum Iran - Poorsafir, Hassan (transcript, 2019)
A sociological look at acceleration and deceleration in Iran. From Babism to the Islamic Revolution.